Protocol for a systematic review assessing the measurement of dietary sodium intake among adults with elevated blood pressure. Issue 1 (3rd January 2022) - Soh, Yee Chang; Yap, Kwong Hsia; McGrattan, Andrea; Yasin, Shajahan; Reidpath, Daniel; Siervo, Mario; Mohan, Devi
Abstract : Introduction: Accurate sodium intake estimates in adults with elevated blood pressure are essential for monitoring salt reduction progress and preventing cardiovascular diseases. However, sodium assessments are challenging in this high-risk population because many commonly used antihypertensive drugs alter urinary sodium excretion. Despite the high cost and substantial participant burden of gold-standard 24-hour urine collection, the relative performance of existing spot-urine based equations and dietary self-report instruments have not been well studied in this population, who will benefit from salt restriction. This systematic review aims to describe the current methods of assessing dietary sodium intake in adults with elevated blood pressure and determine what method can provide a valid and accurate estimate of sodium intake compared with the gold standard 24-hour urine collection. Methods and analysis: Studies assessing sodium intake in adults aged 18 years and above with reported elevated blood pressure will be included. Five electronic databases (MEDLINE, Embase, Global Health, WoS and Cochrane CENTRAL) will be systematically searched from inception to March 2021. Also, a manual search of bibliographies and grey literature will be conducted. Two reviewers will screen the records independently for eligibility. One reviewer will extract all data, and two others will review the extracted data for accuracy. The methodological quality of included studies will be evaluated based on three scoring systems: (1) National Heart, Lung and Blood Institute for interventional studies; (2) Biomarker-based Cross-sectional Studies for biomarker-based observational studies and (3) European Micronutrient Recommendation Aligned Network of Excellence for validation studies of dietary self-report instruments. Ethics and dissemination: As the proposed systematic review will collect and analyse secondary data associated with individuals, there will be no ethical approval requirement. Findings will be disseminated in a peer-reviewed journal or presented at a conference. PROSPERO registration number: CRD42020176137.